STRENGTHENING BUMDES BAROKAH THROUGH SOCIAL MEDIA - Rahayu, Sri Mengesti; Anjarwi, Astri Warih; Anggoro, Damas Dwi (Profit: Jurnal Adminsitrasi Bisnis, 2022)
The community service activity in 2021, entitled "Strengthening BUMDes Barokah Through Social Media," is a follow-up to community service activities in 2020 with the theme "Company Profile as a Means of Increasing Competitiveness of BUMDes Barokah." The output achieved last year with an increase in the number of visitors in 2019-2020 proves that the company profile and Sumber Sira booklet, which is one of the business units in the Barokah BUMDes, have helped strengthen tourism competitiveness, especially in Malang Regency. Based on this background, the community service team will continue efforts to strengthen this competitiveness through social media, especially Instagram, so it is hoped that the Barokah BUMDes management will be more efficient in promoting all their business units and can increase the opinion of Barokah BUMDes.